Effect of Exghange Learning with two Styles Variable and Stable Exercise In Learing Some basic Skills Of Attack Of basketball - Ali , Donea (Journal of Physical Education, 2012)
is the learing process in the country specialty to motor learing skills depend on methods and styles underdeveloped. aim of research making suggested program of learninig of exghange learning with two styles variable and stable exercise to learing some skills of attack of basketball. hypothesis of research there are differences that have statistic function between pre – tests and post – tests for experimental two groups and Control group – in learing some skills of attack of basket ball .